2020
DOI: 10.3390/w12123450
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Environmental Quality of Mediterranean Coastal Lagoons Using Persistent Organic Pollutants and Metals in Thick-Lipped Grey Mullet

Abstract: The evaluation of past and present anthropogenic impacts affecting the ecological quality status of transitional ecosystems is crucial from the perspective of protecting them from further deterioration, and to evaluate remediation and restoration measures. Contamination patterns of thick-lipped grey mullet from two Mediterranean coastal lagoons within a protected area in Italy were assessed and compared in order to evaluate their overall quality status and to collect information that can provide useful feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Regardless of the differences between species and indications of rare spatial differences, the overall element levels in the muscle tissues of six fish species from the Raša River were comparable to or lower than the reported data for low-contaminated freshwater systems [ 9 , 19 , 27 , 43 , 44 , 45 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 74 , 76 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ,…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the differences between species and indications of rare spatial differences, the overall element levels in the muscle tissues of six fish species from the Raša River were comparable to or lower than the reported data for low-contaminated freshwater systems [ 9 , 19 , 27 , 43 , 44 , 45 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 74 , 76 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ,…”
Section: Resultsmentioning
confidence: 99%
“…The presence of E. coli in fish muscle was a good indicator of human beingsʼ contaminations and this was supported by others [44][45][46] . The number of S. aureus in 1 gram of Valamugil seheli muscles during the year seasons was in the range 1.0-3.3 log CFU gG 1 . This finding was comparable to other reports [47][48][49] .…”
Section: Discussionmentioning
confidence: 97%
“…seheli : The results of bacterial types in V. seheli showed that there were significant differences (p<0.05) in the bacterial total count, total coliform, Escherichia coli and Staphylococcus aureus except for Vibrio parahaemolyticus and Salmonella sp. These result showed that the highest value of total bacterial count was in summer (4.3 log CFU gG 1 ), whereas the lowest value was achieved in winter (3.18 log CFU gG 1 ). The result of total coliform showed that the highest value was found in summer (188 MPN), whereas the lowest value was achieved in winter (21.2 MPN).…”
Section: Evaluation Of Pathogenic Microorganisms In Valamugilmentioning
confidence: 89%
See 1 more Smart Citation
“…The recent boost due to the implementation of the Water Framework Directive helped to bring attention to these tools, but there is still a limited number of applications for fish fauna in transitional waters, in particular with only few examples available for coastal lagoons [10]. In order to analyze the sensitivity to human impacts, quantitative assessments of the anthropogenic pressures acting on transitional ecosystems have been carried out [16][17][18][19][20][21][22][23][24][25]. Different methodologies for the assessment of the ecological status of transitional waters have been developed for the Atlantic region [25,26], but most methods that have been proposed for the Mediterranean were not focused on small coastal lakes [20,27,28].…”
Section: Introductionmentioning
confidence: 99%